The misadventures of the family Fletcher - Levy, Dana Alison (Delacorte Press, 2014)
Relates the adventures of a family with two fathers, four adopted boys, and a variety of pets as they make their way through a school year, Kindergarten through sixth grade, and deal with a grumpy new neighbor.